Investigation of Macrobending Losses in Single Mode Optical Fiber - Han, War War Moe Myint; Hla, Tin Tin (The Indonesian Journal of Computer Science, 2025)
Microbending losses are initiated by bending the optical fiber and caused escaping the light from the cladding and core. Macrobending losses degrade the signal quality in long-haul data communication. In the proposed system, macrobending losses are measured by different bending diameters of patch cord single-mode fiber G.652 optical fiber cable by using an Optical Time Domain Reflectometer (OTDR) and an optical power meter to identify the bending losses. The investigation of macro-bending losses aims to analyze the signal power loss in single-mode fiber. The proposed system is investigated by measuring the optical power losses at different bending diameters ranging from 200 mm to 80 mm and the number of turns up to 5 turns and comparison of losses variation for wavelengths 1310 nm and 1550 nm, which are affected by macrobending. The results are compared with theoretical calculations and the practical measurements.